Mesotherapy improves range of motion in patients with rotator cuff tendinitis - Sposito, Maria Matilde de Melo; Rivera, Daniele; Metsavaht, Leonardo (Acta Fisiátrica, 2011)
There is published evidence on the effect of mesotherapy for inflammatory shoulder diseases. Objective: Evaluate the gain in range of motion (ROM) in patients with rotator cuff tendinopathy treated with mesotherapy. A retrospective series of cases conducted from medical records. Location: an outpatient rehabilitation and orthopedic service. 145 patients with clinical diagnosis of rotator cuff tendinopathy, with limited active range of motion. Method: The study subjects were treated with mesotherapy between 1995 and 2008, the blends were selected according to the patient’s profile and tolerance. The effect on the ROM was qualified as “not improved” or “improved”. The improvement in symptomatology was correlated to age, duration of symptoms, and drugs used in the mesotherapy. The concomitant application of physical therapy was also correlated with the result. The adverse effects were evaluated systematically. Results: 117 patients (80.7%) presented objective improvement of ROM or of pain. The result was not influenced by age, duration of symptoms, or by the concomitant application of physical therapy. Only smaller adverse effects were observed. Conclusion: This study suggests that mesotherapy can be efficient in the treatment of rotator cuff tendinopathy, for the improvement of pain, ROM, or global functioning of the upper limb. The clinical impact of this study is that mesotherapy can be associated with the standard physical therapy treatment to improve ROM and pain in rotator cuff tendinopathy.